2002
DOI: 10.1002/bies.10115
|View full text |Cite
|
Sign up to set email alerts
|

Myoblast fusion in Drosophila

Abstract: Somatic muscle formation is an unusual process as it requires the cells involved, the myoblasts, to relinquish their individual state and fuse with one another to form a syncitial muscle fiber. The potential use of myoblast fusion therapies to rebuild damaged muscles has generated continuing interest in elucidating the molecular basis of the fusion process. Yet, until recently, few of the molecular players involved in this process had been identified. Now, however, it has been possible to couple a detailed und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 51 publications
(65 reference statements)
0
50
0
1
Order By: Relevance
“…This arrangement underlies the amazingly similar patterns of immunoreactivity in the eye disc, wing disc and somatic muscle as well as in the pupal optic lobe (Bao and Cagan, 2005;Dworak and Sink, 2002;Fischbach et al, 2009). We also found that these proteins are located in opposing cell membranes in the lamina.…”
Section: Possible Conserved Roles Of the Restricted Domains Of Nephrimentioning
confidence: 70%
“…This arrangement underlies the amazingly similar patterns of immunoreactivity in the eye disc, wing disc and somatic muscle as well as in the pupal optic lobe (Bao and Cagan, 2005;Dworak and Sink, 2002;Fischbach et al, 2009). We also found that these proteins are located in opposing cell membranes in the lamina.…”
Section: Possible Conserved Roles Of the Restricted Domains Of Nephrimentioning
confidence: 70%
“…Myoblast fusion has been studied in mammalian myoblastic cell lines, mice, and Drosophila, and some of the molecules involved have been identified. Genetic screens and biochemical analyses have identified many proteins involved in muscle cell fusion located at the cell surface, in the cytoplasm, and in the nucleus (reviewed in Dworak and Sink, 2002;Taylor, 2002). The membrane proteins implicated in myotube formation in vertebrates include ␤1 integrin, ADAM12 (a member of a disintegrin and metalloproteinase family), NCAM, and M-cadherin (Rosen et al, 1992;Zeschnigk et al, 1995;Fazeli et al, 1996;Huovila et al, 1996;Charlton et al, 2000;Schwander et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…After establishment of myoblast diversity, the fusion process starts, leading in a first fusion step to muscle precursor cells and in a second fusion step to formation of mature myotubes (Doberstein et al, 1997;Rau et al, 2001). This process can be disturbed at distinct levels (reviewed by Dworak and Sink, 2002;Taylor, 2002). Besides lateral inhibition and determination through distinct transcription factors cell-cell signalling is an important mechanism in myogenesis.…”
Section: Introductionmentioning
confidence: 99%